Synthesis of Aragonite Polymorphs from Five Types of Sea Shells by Carbonation Method - Prasetyo Hadi; Wahyu Hidayah; Sani Sani; Srie Muljani (Universitas Islam Raden Rahmat, Malang, 2025)
Shell waste accumulates along the coastal areas of Surabaya and Sidoarjo, with various types of shells including blood shells, green shells, feather shells, kampak shells, and batik shells. Currently, the waste from these shells is not being utilized optimally. Marine shell waste contains more than 95% calcium carbonate (CaCO3), making it suitable for the production of aragonite crystals, which can serve as raw materials for applications such as bone regeneration, paper manufacturing, and as fillers in rubber and plastics. The objective of this research is to synthesize aragonite from five types of marine shells and to investigate the effect of carbonation temperature on the percentage of aragonite formation. The method employed for synthesizing aragonite crystals is carbonation. Initially, the CaCO3 derived from marine shells is calcined at 900°C to produce calcium oxide (CaO). This calcium oxide is then dissolved in hydrochloric acid (HCl) to form calcium chloride (CaCl2). Subsequently, sodium hydroxide (NaOH) is added to CaCl2, and carbon dioxide (CO2) gas is bubbled through the solution to precipitate CaCO3 along with by-products of NaCl and water. The variables examined include comparisons among five types of shells (blood shells, green shells, feather shells, kampak shells, and batik shells) at calcination temperatures of 30°C, 60°C, and 90°C. The best results were obtained from the synthesis using green shells, yielding an aragonite crystal polymorph percentage of 76.4% at a carbonation temperature of 90°C. Conversely, the smallest yield of aragonite crystal polymorph was observed with batik shells at 26.0%.